Perancangan dan Implementasi Sistem Informasi Sarana Prasarana Berbasis Web Menggunakan Metode Rapid Application Development (Studi Kasus: SMAN 10 Pandeglang) - Cecep Suhendar; Sidik Abdul Aziz; Dandi Helyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Facilities and infrastructure are important components in supporting educational activities. Manual inventory management often causes data loss, recording errors, difficulties in data retrieval, and inefficient reporting processes. SMAN 10 Pandeglang still manages facilities and infrastructure using manual record books. This study aims to design and develop a web-based Facilities and Infrastructure Inventory Information System using the Rapid Application Development (RAD) method. The system was developed using Laravel Framework and MySQL Database. The results show that the proposed system improves inventory management efficiency, accelerates reporting processes, facilitates asset monitoring, and minimizes data recording errors.